1979
DOI: 10.1073/pnas.76.2.837
|View full text |Cite
|
Sign up to set email alerts
|

Electrical currents through full-grown and maturing Xenopus oocytes.

Abstract: An extracellular vibrating electrode was used to map the current pattern around Xenopus laevis oocytes. Current was found to enter the animal hemisphere and leave the vegetal hemisphere; in fully grown oocytes from which the follicle cells had been removed, the maximal current density was about 1 uA/cm2. This current decreased to nearly zero in response to progesterone and several other maturation-producing agents. In the case of progesterone, the decline began within a few minutes of the addition of the hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 24 publications
(23 reference statements)
1
47
0
Order By: Relevance
“…It is interesting that an increase in Cl permeability has also been implicated in the generation of the activation potential in Bufo eggs (Maeno, 1959) and in ACh-induced depolarizations in mouse oocytes (Eusebi et al 1979). Furthermore, a steady polar current flow, from animal to vegetal hemispheres, occures in fully grown Xenopus oocytes and here again Cl ions act as the major current carrier (Robinson, 1979). It would be interesting to know if the channels involved in all these cases are different, or are the same but are gated by different processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that an increase in Cl permeability has also been implicated in the generation of the activation potential in Bufo eggs (Maeno, 1959) and in ACh-induced depolarizations in mouse oocytes (Eusebi et al 1979). Furthermore, a steady polar current flow, from animal to vegetal hemispheres, occures in fully grown Xenopus oocytes and here again Cl ions act as the major current carrier (Robinson, 1979). It would be interesting to know if the channels involved in all these cases are different, or are the same but are gated by different processes.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus laevis, the ability to respond to neurotransmitters is related to chloride channels which generate a steady current in the early immature oocyte. Earlier studies by Robinson [1979] suggested that the electric field generated by chloride channels may serve to localize components in the growing oocyte and, more generally, these electrical currents might play a role in the establishment of cell polarity during oogenesis. In Xenopus, voltage-sensitive ion channels, selective for sodium and capable of generating action potentials, were shown to first appear during oocyte growth [Baud 1983].…”
Section: Ion Currents In Vertebrate Oocyte Maturationmentioning
confidence: 99%
“…The Cl-dependent egg-activation potential in Rana has been elicited with Ca ionophore (Schlichter & Elinson, 1981) and by intracellular Ca injection (Cross, 1981). And the standing current in Xenopu8 oocytes has been blocked by treatments expected to block Ca entry (Robinson, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In the amphibian oocyte recent experiments have suggested that variations in Cl permeability may be involved in a number of processes associated with the cell membrane. These include responses to acetylcholine (Xenopu8: Kusano, Miledi & Stinnakre, 1977, to adenosine (Xenopwu: Lotan, Dascal, Cohen & Lass, 1982), and to fertilization and activation (Bufo: Maeno, 1959;Ito, 1972;Rana: Cross & Elinson, 1980; Xenopws: Grey, Bastiani, Webb & Schertel, 1982), and a standing electrical current found in immature oocytes (Xenopuw: Robinson, 1979).…”
Section: Introductionmentioning
confidence: 99%